Manejo sostenible de la broca del café (Hypothenemus hampei) mediante poda sistemática del cafeto en Costa Rica - Rojas, Mainor (2013)
Sustainable management of coffee berryborer (Hypothenemus hampei) by systematicpruning of coffee plants. Assessments wereperformed in 29 coffee plantations in 9 locationsin Costa Rica and a field trial was conducted,with the purpose of studying the behavior of thecoffee berry borer attack in plots with differentpruning systems and validating the differentiatedpest control in a row-pruning (every 3 years)system. The assessment of the coffee berry borer,in sites where pruning is performed per plot every3 years, showed a reduction of 48 percent in theattacks to 1-year branches in relation to the 2-yearbranches; in plots where row pruning is performedevery 4 years, attacks were 52 and 65 percent lessin 1 and 2-year branches than in 3-year branches. A similar effect was observed in plots with rowpruning every 3 years, where 1-year branches hadan average of 56 percent less attack than 2-yearbranches. In the field trial, after the differentiatedapplication of insecticide, the percentage of fruitswith coffee berry borers alive in the 2-year rowwas of 0.7 percent in both treatments at 90 daysafter application; whereas in the 1-year row thispercentage was 0.7 percent where the insecticidewas applied and 1 percent where it was notapplied, with no significant differences betweentreatments. The differentiated control of the coffee berry borer, in a pruning system per rowperformed every 3 years, made it possible to save30% in application time, 40% in insecticide and36.5% in water used for aspersion, by making theapplication to only 33% of the coffee plantation,and without putting into risk the rest of the areacultivated. It was concluded that pruning perplot, as well as per row, makes it possible toconcentrate the coffee berry borer in small areasof the coffee plantation, which contributes to pestcontrol management.